Breast feeding and timing of puberty in boys and girls: A nationwide cohort study. Issue 5 (26th May 2021) - Hvidt, Julie J.; Brix, Nis; Ernst, Andreas; Lunddorf, Lea L.H.; Ramlau‐Hansen, Cecilia H.
Abstract: Background: Breast feeding has been associated with improved infant health, but its impact on pubertal timing remains uncertain, particularly in boys. Objective: The objective of this study was to investigate the association between duration of breast feeding and pubertal timing in boys and girls. Methods: This population‐based cohort study included 13 511 boys and girls from the Puberty Cohort nested within the Danish National Birth Cohort. The children gave half‐yearly, self‐reported information on pubertal development through questionnaires (Tanner stages, age at menarche, first ejaculation, voice break, axillary hair growth, and acne). Information on breast feeding was provided by the mothers when the children were 6 months of age. We estimated mean differences (in months) in age at attaining each pubertal marker and for overall timing of puberty (combined estimate) for every additional month of exclusive breast feeding. Furthermore, we estimated differences in pubertal age when comparing children never exclusively breastfed and exclusively breastfed <4 months using children exclusively breastfed ≥4 months as reference. In sub‐analyses, we further adjusted for infant weight gain and childhood BMI at 7 years to investigate whether these variables mediated the association. Results: Boys tended to reach pubertal markers later for every additional month of exclusive breast feeding (combined estimate: 0.2 (95% confidence interval [CI] 0.0, 0.4 months). Never exclusively breastfed boys reached pubertal markers earlier than the boys exclusively breastfed ≥4 months (combined estimate: −4.1 (95% CI −6.7, −1.6) months). Boys exclusively breastfed <4 months also reached pubertal markers earlier than those never exclusively breastfed but with smaller differences. In girls, duration of breast feeding was not associated with pubertal development. When including infant weight gain or childhood BMI, the results remained essentially unchanged. Conclusions: Shorter duration of exclusive breast feeding was associated with earlier pubertal development in boys but not in girls.